Status, signalling and positional competition - Lisik, MJ (2018)
The first chapter analyses a game between the desired and undesired agents and the Decision Maker (DM), who only wants to admit the desired agents. To influence the DM’s decision, both types of agents can purchase an ostentatious good at the same price, yet the undesired agent sometimes fails to make the right impression. I investigate how the imposition of a capacity constraint can improve the outcomes for the DM. I show that committing to ignore the message received from the agent is an even better policy for the DM. I then add a second, counterfeit good to the model, which is cheaper than the original and only guarantees success with the same, low probability for both types. I show that while full separation might not be obtainable where it used to be without counterfeits, the DM’s expected payoff may increase compared to the baseline model. The second chapter analyses markets in which several ex-ante identical brands are of- fered and then purchased by status-conscious consumers. In equilibrium, the brands are acquired by agents with different incomes and their quality, or the status they confer, is thus ex-ante differentiated. I analyse different market structures and provide comparisons vis-a-vis benchmark models of product differentiation. When status matters even to the poorest agent, the monopolist over-produces each brand, which can be rectified by a flat per-unit tax. Moreover, while an equilibrium does not always exist in more competitive market structures, I find that sequential entry and large enough differences in cost structures are sufficient to guarantee one. In such equilibria, however, both consumer surplus and total welfare are lower than they would be under a monopoly. In the third chapter, I build a model of cardinal positional competition, in which agents compare their own positional consumption to the average positional consump- tion. In equilibrium, agents over-consume compared to the social optimum and lower average positional consumption increases the utilities of all agents. An increase in income inequality raises the average positional consumption if the demand for the positional good is convex in income. I then apply the model in a scenario where agents first have to join one of potentially heterogeneous communities, and only then engage in the positional competition against their fellow community members. I find that moderate differences in qualities of the communities are necessary to support a stratified equilibrium. If assignment to the communities is externally determined, any relocation of agents from the richer to the poorer community reduces average positional consumption in both communities.